2018
DOI: 10.1111/phpp.12383
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy as a first‐line treatment for early‐stage mycosis fungoides: The results of a large retrospective analysis

Abstract: Our analysis indicates that PUVA leads to better responses and longer relapse-free intervals both in patch- and plaque-stage disease. UVB-NB could be a valid therapeutic alternative for patients with recent disease presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 28 publications
3
29
0
2
Order By: Relevance
“…After applying the selection criteria, 7 articles were selected for analysis (eFigure 1 in the Supplement). [17][18][19][20][21][22][23] The study and baseline characteristics of these studies are summarized in Table 1 and Table 2. There were a total of 527 patients treated with PUVA compared with 251 treated with NBUVB.…”
Section: Search Resultsmentioning
confidence: 99%
“…After applying the selection criteria, 7 articles were selected for analysis (eFigure 1 in the Supplement). [17][18][19][20][21][22][23] The study and baseline characteristics of these studies are summarized in Table 1 and Table 2. There were a total of 527 patients treated with PUVA compared with 251 treated with NBUVB.…”
Section: Search Resultsmentioning
confidence: 99%
“…Pavlosky et al found that patients with skin phototypes I-III reached higher complete remission rates and required a lower dose to achieve complete remission compared to patients with dark phototype (13). In the largest series to date of MF patients treated with phototherapy, only 6 patients with dark phototype received NB-UVB (8). In our study, nineteen patients received NB-UVB therapy.…”
Section: Discussionmentioning
confidence: 75%
“…Questions regarding the efficacy of maintenance phase are still debated (4). Studies comparing recurrence rates in patients who received maintenance phase and those who underwent follow-up are scarce including a relatively small proportion of patients with dark phototype (phototypes IV-VI) (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Не было найдено значительных [49]. Согласно опубликованным результатам ретроспективного исследования V. Nikolaou и соавт., в которое вошли данные 227 пациентов с грибовидном микозом на ранних стадиях, уровень достижения полной ремиссии у больных, получающих ПУВА-терапию, был выше на 25 % по сравнению с таковым у больных после УФВ-311 нм (74,5 % против 55,9 % соответственно) [50]. В январе 2019 г. в журнале JAMA Dermatology были опубликованы результаты крупного ретроспективного исследования сравнительной эффективности УФВ-311 нм и ПУВА-терапии у больных грибовидным микозом на стадиях IA-IIA [51].…”
Section: Introductionunclassified
“…Авторы выполнили метаанализ данных 778 больных из 7 ранее проведенных ретроспективных исследований, при выборе пациентов учитывалась стадия заболевания (IA-IIA), а также в целях объективизации результатов отбирались пациенты со схожими режимами назначения УФВ-311 нм и ПУВА-терапии (табл. 5) [47][48][49][50][52][53][54].…”
Section: Introductionunclassified